Immunohistochemical evaluation of oestrogen receptors α and β in epithelium of the vaginal mucous membrane in women after oestrogen therapy - Sawczuk, Beata; Gołębiewska, Maria; Mazurek, Andrzej; Chyczewski, Lech (Menopause Review/Przegląd Menopauzalny, 2017)
Oestrogens act on target cells through α and β receptors (ERα and ERβ). Expression of oestrogen receptors is associated with the age and menopausal condition of women. The aim of the study was an immunohistochemical evaluation of ERα and ERβ receptors in epithelium of the vaginal mucous membrane of women subjected to different forms of hormonal therapy (HTM). Oestrogen receptors ERα and ERβ were identified using immunohistochemical methods and evaluated in smears of vaginal mucous membranes collected from 60 patients subjected to HTM (including 20 patients after oral therapy, 20 patients after transdermal therapy, and 20 patients after vaginal therapy). The results showed a significant change in immunoreactivity of both studied receptors after three months of hormone therapy. The biggest differences in the changes of intensity of ERα and ERβ reactions were observed in patients subjected to vaginal therapy. Immunostaining for α receptor showed differences between three types of hormone therapy. The highest increase in the overall intensity occurred after three months of topical therapy. Immunostaining for Erβ also varied for different types of hormone therapy. The results indicate that hormone therapy administered vaginally is the most effective in the treatment of urogenital ailments during menopause. In addition, topical therapy eliminates adverse effects of systemic oestrogen.